Psoriasis to Psoriatic Arthritis: The Application of Proteomics Technologies - Qi, Fei; Tan, Yaqi; Yao, Amin; Yang, Xutong; He, Yanling (Frontiers in Medicine, 2021)
Psoriatic disease (PsD) is a spectrum of diseases that affect both skin (cutaneous psoriasis: PsC) and musculoskeletal features (psoriatic arthritis PsA). A considerable number of patients with cutaneous psoriasis have asymptomatic synovio-entheseal inflammations, and approximately one-third of those eventually progress to PsA with an enigmatic mechanism. Published studies have shown early interventions to those in very early stage PsA would show effective response to preventing substantial bone destructions or deformities, which suggested an unmet goal for exploring the early PsA biomarkers. The emergence of proteomics technologies brings a whole view of all involved proteins in PsA transitions, offers a unique chance to mapping all potential peptides, and allows a direct head-to-head comparison of interaction pathways in PsC and PsA. This review summarized the latest development of proteomics technologies, highlighted its application in PsA biomarker discovery, and discussed the possible clinical detectable PsA risk factors in PsC patients.